Jawabanmu

2014-08-29T16:23:58+07:00
 \frac{1}{2 \sqrt{3} } +  \frac{1}{2} =  \frac{1+ \sqrt{3} }{2 \sqrt{3} }

\frac{1}{2 \sqrt{2} } + \frac{1}{2} = \frac{1+ \sqrt{2} }{2 \sqrt{2} }

1 *  \frac{1}{2} -  \frac{1}{3 \sqrt{3} }  * 3 = \frac{1}{2} -  \frac{1}{\sqrt{3} } =  \frac{ \sqrt{3} - 2 }{2 \sqrt{3} }

\frac{1}{2\sqrt{3}}*1 -  \frac{1}{3 \sqrt{3} }  * 3 = \frac{1}{2\sqrt{3}} -  \frac{1}{\sqrt{3} } =  \frac{ 3 - 2 }{6 \sqrt{3} } =  \frac{1}{6 \sqrt{3} }
kak no 3 nya mana ..?
nomer 3 sama, aja caranya :3 yang 0x0 diabaikan :3
coba deh